Analisis Aglomerasi Pada Koridor Ekonomi di Indonesia - Firnanda Melia Eriandy (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Economic development that tends to be centered on developed regions causes a spatial concentration of economic activity. One of the efforts to build growth centers in each corridor, the Master Plan for the Acceleration of Expansion of Indonesian Economic Development (MP3EI) divides Indonesia into six economic development corridors. The purpose of this study is to determine the level of economic agglomeration in each economic corridor in Indonesia, and to analyze the determinants of economic agglomeration in these corridors. This type of research data uses secondary data consisting of time series data for 2010-2019 and cross section data of six economic corridors in Indonesia. Data analysis using Herfindahl-Hirschman Index and Panel Data Regression. The results of this study are that the regional government budget has a significant and positive effect on economic agglomeration in economic corridors in Indonesia. The number of workers has a significant and negative relationship to economic agglomeration. Meanwhile, investment does not have a significant positive effect on economic agglomeration in economic corridors in Indonesia. Keywords: Economic Agglomeration, Regional Government Budget, Investment, Herfindahl-Hirschman Index, Panel Data Regression.